Engagement of adolescents in a health communications program to prevent noncommunicable diseases: Multiplicadores Jóvenes, Lima, Perú, 2011. - Diez Canseco, Francisco (2015)
Background: Several risk factors for noncommunicable diseases (NCDs), including obesity, are associated with behaviors established in infancy that persist throughout adolescence and adulthood. As such, adolescents should be engaged in the design and implementation of NCD prevention strategies. Community Context: In Lima, Peru’s capital, the proportion of adolescents aged 15 to 19 is 9.3% of the city’s population, and school enrollment rates are high. The prevalence of excess weight in Peruvian adolescents is 14.2%, and prevalence has not declined in recent years. Also recently, NCDs and their risk factors have gained more attention in public health and policy areas, with regulatory action focusing on healthful nutrition to address obesity and related NCDs. The Multiplicadores Jóvenes (Young Multipliers) project was conducted among adolescents aged 15 to 17 from 9 public secondary schools in peri-urban areas of Lima, Peru. Methods: The project provided basic communication tools and knowledge of NCD prevention and public health research to adolescents during 16 weekly participatory sessions to enable them to design and disseminate healthful lifestyle promotion messages to their school peers. Outcome: Thirty of 45 participants finished the program. Seven communications campaigns were designed and implemented in schools, reaching 1,200 students. The participants gained motivation, increased knowledge, and developed communication skills that were combined to implement healthful lifestyle promotion campaigns. Interpretation: Engaging young people in public health promotion activities was feasible and advantageous for the design of tailored prevention-related content and its dissemination among peers.